Methylation reactions of quinazolin-4-thione - Nazira Boliqul qizi Juraqulova; F.E.Saitkulov; B.J.Elmuradov (Zien Journals, 2024)
methylation of quinazoline-4-thione with methyl iodide, dimethylsulfate and methyltosylate in various solvents was studied. It is shown that the reaction proceeds to N3, O4 and N1 atoms depending on the nature of the alkylating agent, solvent and temperature.
Keywords: Quinazolin-4-thione; Reaction; alkylating agent; solvent nature